Jendela ke Stabilitas: Analisis Rasio Likuiditas dalam Kinerja Keuangan - Nurjamila, SY.; Yahya, Yodi; Jusnia, Jusnia; Sapada, Mh. Iqbal Andi (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
Based on the research that has been carried out, the aim of this research is to determine and evaluate financial ratios in assessing financial performance at PT. Bank Sulselbar Mamasa Branch. The assessment approach used is a descriptive approach. Meanwhile, the type of data used is quantitative data in the form of numbers and the data source used is the financial report of PT. Bank Sulselbar Mamasa Branch. The data collection technique used is the documentation technique and the data analysis technique is the description analysis technique. The results of research at PT. Bank Sulselbar Mamasa Branch proves that in terms of liquidity ratios, especially the current ratio if averaged (4.4 times) and the quick ratio if averaged (4.4 times), then the bank is said to be good because it is above standard criteria. For the cash ratio calculation, if it is averaged (0.05%), the bank is said to be not good because it is below industry standards.